1993
DOI: 10.1002/ajhb.1310050302
|View full text |Cite
|
Sign up to set email alerts
|

The onset of puberty and the availability of sex steroids in female gymnasts

Abstract: Plasma levels of gonadotropins, (sex) steroids, SHBG bound fractions of 17β-estradiol (E2) and testosterone (T), and sex-hormone-binding globulin (SHBG) were compared at the onset of puberty in female gymnasts (n = 7) and two groups of schoolgirls with similar anthropometric characteristics. Ten schoolgirls were matched to the gymnasts on the basis of a sum of skinfolds and the waist/hip ratio, while 12 other girls were selected on the basis of the stature and bicristal breadth of the female gymnasts. All girl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
2
2
0
Order By: Relevance
“…A possible explanation of this phenomenon can be lower levels of estrogens related to a delayed onset of puberty. Also girls who exhibit lower values of estradiol had a narrower pelvis in comparison with the average weight females of the same age (De Ridder et al, 1993). In consistency with this, we observed that male adolescents with higher body fat and with that related elevated levels of estrogens tend to have a relatively wider pelvis and lower overall androgenic status in adulthood.…”
Section: Discussionsupporting
confidence: 86%
“…A possible explanation of this phenomenon can be lower levels of estrogens related to a delayed onset of puberty. Also girls who exhibit lower values of estradiol had a narrower pelvis in comparison with the average weight females of the same age (De Ridder et al, 1993). In consistency with this, we observed that male adolescents with higher body fat and with that related elevated levels of estrogens tend to have a relatively wider pelvis and lower overall androgenic status in adulthood.…”
Section: Discussionsupporting
confidence: 86%
“…A possible explanation of this phenomenon can be lower levels of estrogens related to a delayed onset of puberty. Also girls who exhibit lower values of estradiol had a narrower pelvis in comparison with the average weight females of the same age (de Ridder et al, 1993). In consistency with this, we observed PeerJ reviewing PDF | (2019:09:41138:2:0:NEW 6 Mar 2020)…”
Section: Discussionsupporting
confidence: 83%
“…Since estrogens mediate the progress of female pubertal development 22 , the absence of menarche observed in gymnasts can be explain by the low oestradiol and progesterone levels ( Table 2). Moreover, De Ridder et al 19 showed that low energy intake, daily fibre intake and iron status have a negative effect on gonadal hormone concentrations. In our study, the nutritional intake of the gymnasts was lower than the French recommendations 14 (Table 4) regardless of the period of the investigation.…”
Section: Hormonal Variablesmentioning
confidence: 98%